Anomeric specificity of the monosaccharide carrier in yeasts and yeast-like organisms - Ehwald, R; Mavrina, L (Folia microbiologica, 1981)
The anomeric specificity of monosaccharide uptake was investigated in 42 species of yeasts and related mycelium-forming fungi. Differences in the uptake of anomers were determined by the following methods. (1) Shift of anomeric equilibrium in the outer medium caused by preferential uptake of one of the anomeric forms was monitored polarimetrically as induced mutarotation. (2) The uptake of 14C-D-glucose by cells was examined after addition of freshly prepared solutions of alpha- or beta-D-glucose. Most of the organisms examined display the Saccharomyces-type preference for the alpha-anomers of glucose and xylose which is caused by the higher affinity of the monosaccharide carrier for the alpha-pyranose configuration. The following genera show this type of preference (the number of species is given in parenthesis): Saccharomyces (5), Schizosaccharomyces (1), Endomycopsis (2), Eremascus (1), Endomyces (1), Pichia (1), Hansenula (1), Debaryomyces (2), Lipomyces (1), Willia (1), Nematospora (1), Kluyveromyces (2), Candida (5), Torulopsis (5), Cryptococcus (1). No anomeric specificity was shown by the following genera: Nadsonia (1), Dipodascus (2), Rhodotorula (5), Sporobolomyces (2), Bullera (1), Rhodosporidium (1). A parallel investigation of the concentration dependence of glucose uptake indicates that most yeasts possess a constitutive monosaccharide carrier characterized by the following features: a high maximum rate of uptake, a relatively low affinity, and preference for alpha-anomers. Besides this carrier the majority of these microorganisms possess a glucose-transporting carrier with a higher affinity and a lower capacity.
Keywords: transportní proteiny; aktivní transport; houby; druhová specificita; Monosaccharides; Xylose; Yeasts; Species Specificity; Stereoisomerism; xylosa; stereoizomerie; Fungi; monosacharidy; Carrier Proteins; proteiny přenášející monosacharidy; kvasinky; Biological Transport, Active; glukosa; Glucose; Monosaccharide Transport Proteins